Violation of the rights of consumers of financial services - Galych , Roman (FINANCIAL AND CREDIT SYSTEMS: PROSPECTS FOR DEVELOPMENT, 2025)
The article is devoted to the study of relationships that arise in the process of providing financial services by various financial institutions, as a result of which violations of consumer rights occur or may occur, taking into account current conditions. Problem statement. The relevance of studying consumer rights violations in the field of financial services is undeniable in the modern world, especially with the growth of service users in cyberspace. However, the growing complexity of financial products and services requires a high level of consumer protection. Today, consumer rights violations in the financial sector can have serious consequences, including financial losses, loss of trust in financial institutions and socio-economic problems for consumers, and as a consequence, for the security of the financial system and the state. Unresolved aspects of the problem. Thus, as seen, the study and analysis of problems related to violations of the rights of consumers of financial services and certain aspects of their prevention are relevant and important today. At the same time, we believe that the attention paid in previous studies is not comprehensive and requires consideration of certain aspects of violations of consumer rights and the search for appropriate solutions at the level of management, legislative initiatives, etc. Purpose of the article. The goal of the work, in turn, is to develop a systematic approach to solving problems related to the violation of the rights of consumers of financial services. Presentation of the main material. Particular attention is paid to such key problems as opaque contract terms, the impact of misleading advertising, excessive promises of investment returns is investigated, and the problem of illegal charges and commissions is also considered. Fraudulent actions and cybercrimes, such as the use of fraudulent schemes or forgery of documents. The article also considers the role of the Office for Financial Services Consumer Rights Protection. We use the following scientific methods: induction, deduction, comparative, systematisation method. Conclusions. The study presents a systematic approach to solving the problem of violations of the rights of consumers of financial services. This, as expected, will relieve the judicial system, inspire confidence in potential consumers, promote technological progress, ensure the stability of the financial system, and ultimately establish Ukraine as a social, democratic, and legal state.